Impact of sarcopenia in the elderly and the importance of food and nutrition education (Research, Society and Development, 2025)
Introduction: Sarcopenia is a medical condition characterized by the progressive loss of muscle mass and strength. When associated with aging, it is associated with a higher risk of falls, hospitalization, and mortality. Objective The general objective of this article is: to analyze the impacts of food and nutritional education on the prevention and treatment of sarcopenia in the elderly. Methodology: This study was conducted through a literature review. Scientific documents were selected, selecting works published in the last 10 years (between 2015 and 2025) in Portuguese and English. The databases used were PubMed and SciELO. Discussion: Studies indicate that nutritional education, when combined with adequate protein intake (≥1.2 g/kg/day), becomes an effective tool in the prevention and treatment of sarcopenia. Data that reinforce its importance as a priority and essential intervention due to the aging population. Furthermore, incorporating EAN into public policies and health services can play a fundamental role in promoting healthy aging. Final considerations: Sarcopenia, recognized by ICD-10 (M62.84), is one of the greatest public health challenges, given its impact on the autonomy and quality of life of older adults. Population aging, combined with poor eating habits, increases the relevance of preventive strategies. In this context, Food and Nutrition Education (EAN) emerges as a fundamental tool, capable of promoting healthy food choices, preserving functionality, and reducing psychosocial impacts.